Encounters and the Diasporic Art of Africa: An Interview with Allyson Purpura, Curator of African Art, Krannert Art Museum, University of Illinois - Habib, Jasmin (Anthropologica, 2014)
In this paper, Jasmin Habib interviews Allyson Pur pura, Curator of African Art at the Krannert Art Museum about the reinstallation of "Encounters: The Arts of Africa." In the interview, they discuss how the objects on display have journeyed across the ocean as well as across epistemological categories tied to colonialism and the expansion of empire. The idea of "encounter" lies at the heart of this exhibition: the sometimes fraught histories of encounters between objects; the repurposing of tradition-based art into contemporary art works; and, of course, the politics of display and the encounter between visitors to the museum and the artworks.